Does Cutting Child Benefits Reduce Fertility in Larger Families? Evidence from the UK's Two-Child Limit - Mary Reader; Jonathan Portes; Ruth Patrick (Institute of Labor Economics (IZA), 2022)
We study the impact of restricting child-related social assistance to the first two children in the family on the fertility of third and subsequent births. As of April 2017, all third and subsequent born children to low-income families in the UK did not receive means-tested child benefits, amounting to a reduction in income relative to the previous system of approximately 3000 GBP a year per child. We use administrative births microdata and household survey data to estimate the impact of the two-child limit on higher-order births with a triple differences approach, exploiting variation over date of birth, socio-economic status, and birth order. We find some evidence that the policy led to a small decline in higher-order fertility among lowincome families. However, compared to earlier research in the UK and elsewhere, largely based on benefit increases, the impact is small. This may be due to informational barriers or to other economic and social constraints affecting low income families. Our results imply that the main impact of cuts to child benefits is not to reduce fertility but to withdraw income from low-income families, with potential implications for child poverty.
Keywords: J13; J18; H31; H53; 330; fertility; family size; social assistance; welfare reform